(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
The purpose of this study was to find similarities and differences in the intrinsic elements of the folklore of Taokala and Sangkuriang. The method used in this study is a qualitative descriptive method with an oral literature approach. The results of the study show the differences and similarities between the folklore of Toakkala and Sangkuriang. (1) The similarities are in the characteristic elements of the folklore, setting, mandate, point of view. Characteristics of the folklore Toakkala and Sangkuriang both use animal and human characters. The setting of both folklore is in the old kingdom. The message conveyed by the two stories is not to love excessively. The point of view of the story both use the third person. (2) The differences from the intrinsic elements are found in the theme, plot and setting. The theme in Toakkala’s folklore is about a marriage that is hindered by the blessing of parents, while Sangkuriang’s theme is about incestuous marriage. The plot in the Toakala folklore is a forward plot, while in the Sangkuriang folklore it uses back and forth grooves. The setting of the Toakala folklore is in Bantimurung District, Maros Regency, South Sulawesi Province, while the Sangkuriang folklore is in Lembang District, Bandung Regency, West Java Province.